A battery additive and its preparation method and application
By using porous latex particles as additives for batteries in lithium-ion battery electrodes, the problems of insufficient wetting and liquid retention ability of the electrode sheet are solved, and the circulation performance and safety of the battery are significantly improved.
Patent Information
- Application Number
- CN202211122984.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-15
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-09-15
AI Technical Summary
The insufficiency and liquid retention capacity of the lithium-ion battery electrode sheets lead to difficulty in infiltration of electrolytes, hindering ion transmission, and seriously reducing the battery's circulation performance, rate performance and safety.
Porous latex particles are used as additives for batteries. Pores are made through alkaline substances after reaction of seed emulsion, acid monomer and other monomers, forming pores with rich pore structure and high specific surface area, which is used to enhance the absorption of pole sheets. Liquid performance and liquid retention ability.
Significantly improve the wetting properties and liquid absorption performance of the electrode sheet, shorten the battery liquid injection process time, improve the battery circulation performance and safety, and ensure that the capacity retention rate of lithium-ion batteries for 100 weeks of normal temperature cycle ≥99.0%.
Smart Images

Figure CN115340636B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion battery materials, and in particular relates to a battery additive and a preparation method and application thereof. Background Art
[0002] In order to meet the needs of future electrification, especially the further development of mobile electronic products such as mobile phones, the electric vehicle industry, and other circular energy systems, the performance improvement of lithium-ion batteries also faces huge challenges. At present, the market not only has an increasing demand for lithium-ion batteries, but also gradually increases the performance requirements of lithium-ion batteries, including the increase of battery capacity, the increase of energy density, the increase of battery cycle life, and the shortening of charging time.
[0003] Lithium-ion batteries are usually assembled from positive electrodes, negative electrodes, diaphragms and electrolytes. The quality of the electrodes directly affects the performance of lithium-ion batteries. Most of the electrodes of commercial lithium-ion batteries are prepared by coating a slurry on the surface of the current collector. The slurry contains active substances, conductive additives and binders, etc. The binders are divided into water-based binders and oily binders according to their solubility. In order to obtain lithium-ion batteries with better performance, people have improved the performance of the electrodes. For example, CN110061222A discloses a method for preparing lithium battery slurry and its application. The conductive agent is added to the glue and the active material in batches to obtain a conductive slurry and a premix. The conductive slurry is added to the premix for kneading, vacuum degassing, and battery slurry is obtained; the battery slurry is used to prepare electrodes, especially thick electrodes, with long life and high rate charge and discharge performance. In addition to preparing thick electrodes, the methods commonly used in the industry also include increasing the proportion of active substances in the slurry, increasing the density of the electrodes, etc., thereby increasing the capacity and energy density of lithium-ion batteries. However, electrodes with high energy density usually have poor wettability, which makes it difficult for electrolyte to infiltrate, hinders ion transmission, and causes lithium metal precipitation after use, seriously reducing the battery's cycle performance, rate performance and safety.
[0004] In order to improve the wettability and liquid retention of the electrode, researchers proposed a method of adding a liquid retaining agent to the slurry. For example, CN113611823A discloses a positive electrode. The preparation method of the positive electrode slurry is: dry-mix the positive electrode active material, carbon black conductive agent, binder and liquid retaining agent, then add a dispersant and a solvent, mix and stir evenly to make a positive electrode slurry; wherein the liquid retaining agent is one of polyacrylate, polymethyl methacrylate, polyacrylonitrile, polyacrylamide, and polystyrene. Compared with ordinary thick electrodes, the addition of a liquid retaining agent can improve the wettability and liquid retention to a certain extent, but the effect is relatively limited and cannot solve the cycle performance problem of the electrode and the battery well.
[0005] The impact of battery pole pieces on battery performance is also reflected in the process. In the production process of lithium-ion batteries, there is a process of injecting electrolyte into the battery. The injection process is a very important process in the production of lithium-ion batteries. The accuracy of the injection amount and the efficiency of the injection directly determine the consistency and production efficiency of lithium-ion batteries. At present, the wettability of the pole piece is poor, and due to factors such as winding, lamination, and extrusion, its liquid absorption efficiency is relatively low, requiring a long time to inject liquid, and it is easy to have uneven liquid absorption, which seriously affects the battery production efficiency and yield. At the same time, due to the poor wettability of the pole piece and the limited liquid retention capacity, the electrolyte is consumed quickly during the battery cycle, resulting in poor battery cycle performance.
[0006] Therefore, improving the wettability and liquid retention capacity of the electrode is an urgent problem to be solved in this field. Summary of the invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a battery additive and a preparation method and application thereof. The battery additive has a porous structure and good swelling performance. When used in battery pole pieces, it can significantly improve the liquid absorption and liquid retention capabilities of the pole pieces, thereby improving the performance of lithium-ion batteries.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a battery additive, comprising porous latex particles.
[0010] The battery additive provided by the present invention contains porous latex particles, which have a porous structure and a large specific surface area, and have good swelling properties. The battery additive is used for battery pole pieces. On the one hand, it can improve the liquid absorption performance of the pole pieces, shorten the battery injection process time, thereby increasing production capacity; on the other hand, it improves the infiltration properties of the pole pieces and improves the consistency of the pole piece infiltration electrolyte. Moreover, due to the high swelling performance, the porous latex particles have a large number of gaps to store electrolyte, which can improve the liquid retention capacity of the pole pieces and enhance lithium ion conduction, thereby improving the cycle performance of the battery.
[0011] Preferably, the particle size of the porous latex particles is 0.1-10.0 μm, for example, it can be 0.2 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm, 6.0 μm, 6.5 μm, 7.0 μm, 7.5 μm, 8.0 μm, 8.5 μm, 9.0 μm or 9.5 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0012] Preferably, the specific surface area of the porous latex particles is ≥10m 2 / g, for example, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 50m 2 / g, 80m 2 / g、100m 2 / g, 200m 2 / g、300m 2 / g, 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g, 550m 2 / g、600m 2 / g, 650m 2 / g、700m 2 / g, 750m 2 / g、800m 2 / g, 850m 2 / g、900m 2 / g or 950m 2 / g, etc.
[0013] Preferably, the swelling rate of the porous latex particles is 40%-10000%, for example, it can be 50%, 80%, 100%, 120%, 150%, 180%, 200%, 300%, 500%, 700%, 900%, 1000%, 2000%, 3000%, 4000%, 5000%, 6000%, 7000%, 8000% or 9000%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 100%-10000% is further preferred.
[0014] Exemplarily, the swelling rate is the mass change rate of the porous latex particles after being immersed in an electrolyte at 85° C. for 24 hours.
[0015] Preferably, the porous latex particles are obtained by reacting a seed emulsion, an acidic monomer and other monomers and then forming pores with an alkaline substance.
[0016] As a preferred technical solution of the present invention, the porous latex particles are obtained by reacting a seed emulsion, an acidic monomer and other monomers and then forming pores through an alkaline substance, wherein the acidic monomer and other monomers are compounded and polymerized with the seed emulsion to form polymer particles (latex particles), and under the action of the alkaline substance, the linear polymers formed by the polymerization of the acidic monomers in the polymer particles are dissolved, thereby generating abundant pores to obtain the porous latex particles.
[0017] Preferably, the seed emulsion may be a conventional polymer emulsion, which can be purchased from the market.
[0018] Preferably, the seed emulsion includes any one of pure acrylic emulsion, styrene acrylic emulsion, acetate acrylic emulsion, silicone acrylic emulsion, styrene butadiene emulsion, nitrile emulsion, polyvinylidene fluoride emulsion or polytetrafluoroethylene emulsion, or a combination of at least two thereof.
[0019] Preferably, the particle size of the latex particles in the seed emulsion is 50-500nm, for example, it can be 60nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm, 420nm, 450nm or 480nm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0020] Preferably, the acidic monomer is a polymerizable monomer containing at least one (eg, one, two or three) of a carboxyl group, a sulfonic acid group or a phosphoric acid group.
[0021] Preferably, the acidic monomer includes any one of acrylic acid (AA), methacrylic acid (MAA), vinyl phosphate or vinyl sulfonic acid, or a combination of at least two thereof.
[0022] Preferably, the other monomer is a polymerizable monomer that does not contain an acidic group (does not contain a carboxyl group, a sulfonic acid group or a phosphoric acid group).
[0023] Preferably, the other monomers are water-insoluble monomers.
[0024] Preferably, the other monomers include any one of styrene (St), (meth)acrylate, acrylonitrile (AN) or vinyl acetate (VAc), or a combination of at least two thereof.
[0025] Preferably, the (meth)acrylate includes any one of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate or pentyl (meth)acrylate, or a combination of at least two thereof.
[0026] Preferably, the mass ratio of the acidic monomer to other monomers is (0.1-10.0):1.0, for example, it can be 0.2:1.0, 0.5:1.0, 0.8:1.0, 1.0:1.0, 2.0:1.0, 3.0:1.0, 4.0:1.0, 5.0:1.0, 6.0:1.0, 7.0:1.0, 8.0:1.0 or 9.0:1.0, and more preferably (1.0-8.0):1.0.
[0027] As a preferred technical solution of the present invention, the mass ratio of the acidic monomer to other monomers is (0.1-10.0):1.0, and further preferably (1.0-8.0):1.0; the two types of monomers polymerize with the seed emulsion to form latex particles, and pores are formed under the action of alkaline substances to form porous latex particles with good pore structure. If the ratio of the acidic monomer to other monomers exceeds the aforementioned range, the amount of the acidic monomer is too small, and porous latex particles with rich pore structure cannot be formed, thereby affecting the liquid absorption and liquid retention performance of the electrode; and when the amount of the acidic monomer is too much and the amount of other monomers is too little, the acidic monomer cannot effectively enter the latex of the seed emulsion, and cannot be well polymerized into latex particles with larger particle size, and porous latex particles with excellent performance cannot be obtained.
[0028] Preferably, the mass ratio of the sum of the mass of the acidic monomer and other monomers to the seed emulsion is 1.0:(0.1-10.0), for example, it can be 1.0:0.2, 1.0:0.3, 1.0:0.4, 1.0:0.5, 1.0:0.6, 1.0:0.7, 1.0:0.8, 1.0:0.9, 1.0:1.0, 1.0:2.0, 1.0:3.0, 1.0:4.0, 1.0:5.0, 1.0:6.0, 1.0:7.0, 1.0:8.0 or 1.0:9.0, etc., and 1.0:(2.0-8.0) is further preferred.
[0029] As a preferred technical solution of the present invention, the mass ratio of the total mass of the two types of monomers to the seed emulsion is 1.0:(0.1-10.0), and further preferably 1.0:(2.0-8.0). The two types of monomers can fully enter the latex of the seed emulsion and polymerize to form latex particles with larger particle sizes, and then form pores under the action of alkaline substances to form porous latex particles with rich pore structures. If the mass ratio of the monomer to the seed emulsion exceeds the preferred range, the amount of the seed emulsion is too much, and the content of the polymer based on the acidic monomer in the latex particles obtained by polymerization is too small, and porous latex particles with rich pore structures cannot be formed, affecting the liquid absorption and liquid retention performance of the electrode; if the amount of the seed emulsion is too little, the excess monomer will cause the latex particles in the seed emulsion to rupture, so it is impossible to polymerize into latex particles with large particle sizes, and it is impossible to obtain ideal porous latex particles.
[0030] In the present invention, the mass of the seed emulsion and its mass ratio to the monomer are calculated based on the solid content thereof, excluding the solvent / dispersant etc. therein.
[0031] In a second aspect, the present invention provides a method for preparing the battery additive as described in the first aspect, the preparation method comprising: reacting a seed emulsion, an acidic monomer and other monomers in the presence of an initiator to obtain a polymer emulsion; mixing the polymer emulsion with an alkaline substance to form pores to obtain the battery additive.
[0032] Preferably, after the seed emulsion, acidic monomer and other monomers are mixed, an initiator is added thereto to carry out a reaction.
[0033] Preferably, the mixing time is 0.1-2.0h, for example, it can be 0.2h, 0.5h, 0.8h, 1.0h, 1.2h, 1.5h or 1.8h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0034] As a preferred technical solution of the present invention, in the preparation method, the seed emulsion, acidic monomers and other monomers are first mixed to allow the seed emulsion to swell and absorb enough monomers (acidic monomers and other monomers), and then an initiator is added thereto to carry out a polymerization reaction to form latex particles with a larger particle size.
[0035] Preferably, the initiator includes a water-soluble azo initiator and / or a persulfate, and more preferably ammonium persulfate.
[0036] Preferably, based on the sum of the masses of the acidic monomer and other monomers as 100%, the mass of the initiator is 0.05-5.00%, for example, it can be 0.08%, 0.10%, 0.30%, 0.50%, 0.80%, 1.00%, 1.50%, 2.00%, 2.50%, 3.00%, 3.50%, 4.00% or 4.50%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0037] Preferably, the reaction temperature is 60-80°C, for example, it can be 61°C, 63°C, 65°C, 68°C, 70°C, 71°C, 73°C, 75°C, 77°C or 79°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0038] Preferably, the reaction time is 1-12 h, for example, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h or 11 h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0039] Preferably, the polymer emulsion is mixed with an alkaline substance to make the pH value of the system 7.0-9.0, for example, the pH value of the system is 7.1, 7.3, 7.5, 7.7, 7.9, 8.0, 8.1, 8.3, 8.5, 8.7 or 8.9, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0040] Preferably, the alkaline substance is a metal hydroxide, more preferably any one of sodium hydroxide, lithium hydroxide or potassium hydroxide, or a combination of at least two thereof.
[0041] Preferably, the alkaline substance is mixed with the polymer emulsion in the form of its aqueous solution.
[0042] Preferably, the pore making time is 0.5-5.0h, for example, it can be 0.8h, 1.0h, 1.2h, 1.5h, 1.8h, 2.0h, 2.2h, 2.5h, 2.8h, 3.0h, 3.2h, 3.5h, 3.8h, 4.0h, 4.2h, 4.5h or 4.8h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0043] Preferably, the preparation method comprises the following steps: after mixing the seed emulsion, acidic monomer and other monomers for 0.1-2.0h, adding an initiator thereto, reacting at 60-80°C for 1-12h to obtain a polymer emulsion; adding an alkaline substance to the polymer emulsion to adjust the pH value of the system to 7.0-9.0, forming pores to form porous latex particles, and obtaining the battery additive.
[0044] In a third aspect, the present invention provides an electrode material composition, wherein the electrode material composition comprises the battery additive as described in the first aspect.
[0045] Preferably, the electrode material composition comprises a combination of an electrode active material, a conductive agent, a binder and the battery additive.
[0046] Preferably, based on 100 parts by mass of the electrode active material, the mass of the battery additive is 0.01-1.00 parts, for example, it can be 0.03 parts, 0.05 parts, 0.08 parts, 0.10 parts, 0.20 parts, 0.30 parts, 0.40 parts, 0.50 parts, 0.60 parts, 0.70 parts, 0.80 parts or 0.90 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0047] Preferably, the electrode active material is a positive electrode active material or a negative electrode active material.
[0048] Preferably, the positive electrode active material includes an active material that can be embedded in and de-embedded with lithium, illustratively including but not limited to: any one of lithium iron phosphate and lithium transition metal composite oxides (such as nickel-cobalt-manganese ternary materials) or a combination of at least two thereof.
[0049] Preferably, the negative electrode active material includes any one of carbon material, silicon-carbon material, silicon-oxygen material, or a combination of at least two of them.
[0050] Preferably, the carbon material includes any one of graphite, carbon black, carbon nanotubes, carbon fibers, mesocarbon microbeads or petroleum coke, or a combination of at least two thereof.
[0051] Preferably, the conductive agent includes any one of carbon black, graphite, carbon nanotubes or carbon fibers, or a combination of at least two of them.
[0052] Preferably, based on 100 parts by mass of the electrode active material, the mass of the conductive agent is 0.1-5.0 parts, for example, it can be 0.1 parts, 0.3 parts, 0.5 parts, 0.7 parts, 0.9 parts, 1.0 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2.0 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3.0 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4.0 parts, 4.2 parts, 4.5 parts or 4.8 parts, etc.
[0053] Preferably, the binder comprises polyvinylidene fluoride (PVDF) or styrene butadiene rubber (SBR).
[0054] Preferably, based on 100 parts by mass of the electrode active material, the mass of the binder is 0.01-5.00 parts, for example, it can be 0.03 parts, 0.05 parts, 0.08 parts, 0.10 parts, 0.30 parts, 0.50 parts, 0.70 parts, 0.90 parts, 1.00 parts, 1.20 parts, 1.50 parts, 1.80 parts, 2.00 parts, 2.20 parts, 2.50 parts, 2.80 parts, 3.00 parts, 3.20 parts, 3.50 parts, 3.80 parts, 4.00 parts, 4.20 parts, 4.50 parts or 4.80 parts, etc.
[0055] Preferably, the electrode material composition further comprises a thickener; the thickener is preferably sodium carboxymethyl cellulose (CMC).
[0056] Preferably, the electrode material composition is a negative electrode material composition, comprising a negative electrode active material, a conductive agent, a binder and the battery additive.
[0057] In a fourth aspect, the present invention provides a battery electrode, comprising a current collector and a coating disposed on the current collector, wherein the material of the coating comprises the electrode material composition as described in the third aspect.
[0058] Preferably, the battery electrode is a negative electrode.
[0059] As a preferred technical solution of the present invention, the negative electrode plate containing the battery additive has good wettability to the electrolyte, and the electrode plate has good consistency in the electrolyte. Through the design and optimization of the components of the battery additive, the liquid absorption time of the negative electrode plate is ≤10s. Compared with ordinary electrodes, the degree of shortening of the liquid absorption time is >70%, thereby significantly shortening the battery injection process. The negative electrode plate containing the battery additive has excellent liquid absorption and liquid retention performance, reduces the consumption of electrolyte during battery cycling, enhances lithium ion conduction, and makes the capacity retention rate of lithium ion batteries ≥99.0% after 100 cycles at room temperature, and has excellent cycle performance.
[0060] In a fifth aspect, the present invention provides an electrochemical energy storage device, comprising at least one of the battery additive as described in the first aspect, the electrode material composition as described in the second aspect, and the battery electrode sheet as described in the third aspect.
[0061] Preferably, the electrochemical energy storage device comprises any one of a lithium ion battery, a sodium ion battery, a supercapacitor, a fuel cell or a solar cell.
[0062] Compared with the prior art, the present invention has the following beneficial effects:
[0063] The battery additive provided by the present invention includes porous latex particles, which have rich pore structure and large specific surface area, and the specific surface area can reach 414.7-572m 2 / g, and has good swelling performance, with a swelling rate of 400-9300%. The battery additive is used for battery pole pieces, which can effectively improve the wettability and liquid absorption performance of the pole pieces, shorten the battery injection process time, and improve production capacity; at the same time, it has a large number of gaps to store electrolyte, significantly improve the liquid retention capacity of the pole pieces, enhance lithium ion conduction, and improve the cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is a scanning electron microscope image of the porous latex particles described in Example 1. DETAILED DESCRIPTION
[0065] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0066] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0067] "Optionally" or "either" means that the subsequently described matter or event can or cannot occur, and that the description includes instances where the event occurs and instances where it does not.
[0068] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0069] The terms "one embodiment", "some embodiments", "exemplarily", "specific examples" or "some examples" described in the present invention mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this document, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.
[0070] Moreover, the technical features involved in various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0071] The seed emulsions involved in the following specific embodiments of the present invention are all commercially available products, such as styrene-acrylic emulsion, styrene-butadiene emulsion, pure acrylic emulsion, nitrile emulsion, acetate-acrylic emulsion and polyvinylidene fluoride (PVDF) emulsion, all of which are purchased from MacLean.
[0072] Example 1
[0073] A battery additive and a preparation method thereof, wherein the battery additive comprises porous latex particles, which are obtained by reacting a seed emulsion (styrene-acrylic emulsion), an acidic monomer (acrylic acid, AA) and other monomers (styrene, St) and then forming pores with an alkaline substance; the mass ratio of the seed emulsion, the acidic monomer and the other monomers is 16:3:1; the specific preparation method is as follows:
[0074] 15 parts of acidic monomer AA and 5 parts of other monomer St are added to 80 parts of seed emulsion (styrene-acrylic emulsion, average particle size of latex particles is 150 nm, and the mass fraction is calculated by solid content), and mixed for 2 hours to allow the seed emulsion to absorb enough monomers, and then 0.1 parts of initiator ammonium persulfate are added, and polymerization reaction is carried out at 70° C. for 6 hours to obtain a polymer emulsion; sodium hydroxide solution is added to the polymer emulsion to adjust the pH value of the system to 8.0, and pores are generated for 1 hour to form porous latex particles to obtain the battery additive.
[0075] Embodiment 2-10
[0076] A battery additive and a preparation method thereof, which differs from Example 1 in that the components of the porous latex particles are different, as specifically shown in Table 1; the "mass ratio" in Table 1 is the mass ratio of the seed emulsion, the acidic monomer and other monomers; the mass of the seed emulsion is measured by its solid content.
[0077] Table 1
[0078] Seed lotion Acidic monomer Other monomers Quality Ratio Example 1 Styrene acrylic emulsion acrylic acid Styrene 16:3:1 Example 2 Styrene Butadiene Emulsion acrylic acid Styrene 15:4:1 Example 3 Pure acrylic emulsion Methacrylic acid Butyl acrylate 17:2:1 Example 4 Nitrile emulsion Vinyl sulfonic acid Acrylonitrile 14:5:1 Example 5 Acrylic Emulsion Vinyl Phosphate Vinyl acetate 16:1:1 Example 6 PVDF emulsion acrylic acid Styrene 14:6:1 Example 7 Styrene acrylic emulsion acrylic acid Styrene 16:1:3 Example 8 Styrene acrylic emulsion acrylic acid Styrene 16:3.8:0.2 Example 9 Styrene acrylic emulsion acrylic acid Styrene 1:3:1 Example 10 Styrene acrylic emulsion acrylic acid Styrene 40:1:3
[0079] Comparative Example 1
[0080] A battery additive is common styrene acrylic latex particles, that is, the latex particles of the seed emulsion in Example 1.
[0081] Comparative Example 2
[0082] A battery additive is styrene-acrylic latex particles, which are obtained by polymerization of seed emulsion (styrene-acrylic emulsion), acrylic acid and styrene, wherein the mass ratio of seed emulsion, acrylic acid and styrene is 16:3:1; the preparation method thereof is different from that of Example 1 only in that no sodium hydroxide solution is added for pore formation; other process parameters are the same as those of Example 1.
[0083] Comparative Example 3
[0084] A battery additive (existing liquid-retaining additive), specifically a linear methyl methacrylate-butadiene-styrene copolymer with a number average molecular weight of 180,000.
[0085] Application Example 1-10, Comparative Application Example 1-3
[0086] A battery pole piece, which is a negative electrode pole piece, comprises a current collector (Cu foil) and a coating arranged on the current collector, wherein the material of the coating is an electrode material composition, comprising a negative electrode active substance (silicon oxide material SiO-450, produced by B&T New Energy Materials Co., Ltd., with a silicon content of 10%), a conductive agent (carbon black SP), a binder (styrene-butadiene rubber, SBR), a thickener (sodium carboxymethyl cellulose, CMC) and the battery additive, with a mass ratio of 96:1:1:1.5:0.5; the battery additive is the battery additive provided in Examples 1-10 and Comparative Examples 1-3, respectively.
[0087] The preparation method of the negative electrode sheet is as follows: the negative electrode active material, the conductive agent, the binder and the thickener, and the battery additive are mixed in a mass ratio of 96:1:1:1.5:0.5, added into deionized water in a ratio of 40wt% of the system solid content, and stirred and mixed to prepare a uniform negative electrode slurry, which is then passed through a 100-mesh screen and coated on a negative electrode current collector Cu foil, and then dried, and rolled using a roller at a speed of 10×10 4 The negative electrode sheet is obtained by rolling with a unit length load of N / m.
[0088] A lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the aforementioned negative electrode sheet; the preparation method of the lithium-ion battery is as follows:
[0089] (1) Preparation of positive electrode sheet: The positive electrode active material (lithium iron phosphate material), conductive carbon black, and binder (PVDF) were mixed in a mass ratio of 95.5:2:2.5 according to the solid content, added into N-methylpyrrolidone (NMP) at a ratio of 50 wt % of the system solid content, and stirred and mixed to prepare a uniform positive electrode slurry. After passing through a 100 mesh sieve, the slurry was coated on the positive electrode current collector Al foil, and then dried. The slurry was rolled using a roller at a speed of 10×10 4 Rolling is performed with a unit length load of N / m to obtain a positive electrode sheet;
[0090] (2) Negative electrode: as described above;
[0091] (3) Diaphragm: PE porous polymer film (Shenzhen Xingyuan Material Technology Co., Ltd.) was used as the diaphragm;
[0092] (4) Assembly of lithium-ion batteries: The positive electrode sheet, the separator, and the negative electrode sheet are wound in sequence to obtain a battery cell; the battery cell is packaged with an aluminum-plastic film, baked to remove water, and then injected with an electrolyte. After vacuum packaging, storage, formation, secondary sealing, shaping, and other processes, the lithium-ion battery is obtained.
[0093] Comparative Application Example 4
[0094] A battery electrode and a lithium-ion battery comprising the same, wherein the battery electrode is a negative electrode electrode, and the only difference between the battery electrode and Application Example 1 is that the coating material (electrode material composition, i.e., negative electrode slurry) does not contain battery additives; other materials, proportions and preparation methods are the same as those in Application Example 1.
[0095] Performance Testing:
[0096] (1) Morphology and specific surface area
[0097] The morphology of the porous latex particles of the battery additive described in the embodiment was tested using a scanning electron microscope (SEM, EVOMA25, Zeiss ZEISS). For example, the scanning electron microscope image of the porous latex particles described in Example 1 is as follows: Figure 1 As shown, from Figure 1 It can be seen that the average particle size of the porous latex particles is 0.6 μm, and the particles contain rich pore structures.
[0098] The multi-point BET method was used to test the specific surface area of the porous latex particles. The testing instrument was a Micromeritics specific surface area tester, and the adsorbent was high-purity N2. The specific surface area data obtained are shown in Table 2.
[0099] (2) Swelling rate
[0100] Add the battery additive to be tested (emulsion containing the porous latex particles) dropwise into a clean mold, ensuring that the solid content is 4g±0.1g, place it in an oven at 70°C for 12h, take out a 1cm×1cm cut piece, weigh the prepared sample, and record the mass M1; weigh enough electrolyte, add it to the glass bottle containing the above sample, ensure that the electrolyte completely immerses the sample, and seal the bottle, and place it in an 85°C water bath for 24h. Take out the sample, wipe off the electrolyte on the sample with clean dust-free paper, weigh the mass of the swollen sample, and record it as M2.
[0101] Swelling rate = 100% × (M2-M1) / M1. The test results are shown in Table 2.
[0102] (3) Liquid absorption performance of the electrode
[0103] 1 mL of electrolyte DMC was dripped onto the negative electrode to be tested. The timing started from the moment when the electrolyte DMC contacted the electrode and ended when the electrolyte was completely absorbed by the electrode. The electrode absorption time was recorded, as shown in Table 2.
[0104] (4) Battery cycle performance
[0105] The prepared lithium-ion battery was charged to 4.2V at a constant current of 0.33C, then charged to a cut-off current of 0.02C at a constant voltage, and discharged to 2.5V at 0.33C; left for 5 minutes, charged to 4.2V at a constant current of 0.33C, then charged to a cut-off current of 0.02C at a constant voltage, and discharged to 2.5V at 0.33C, thereby performing initial adjustment;
[0106] At 25°C, the initially adjusted lithium-ion battery is charged to 4.2V at 0.5C constant current, then charged to a cut-off current of 0.02C at constant voltage, left for 5 minutes, and then discharged to 2.5V at 1C constant current, left for 5 minutes, and the first cycle discharge capacity is measured. After 100 cycles of charge / discharge, the 100th cycle discharge capacity is measured, and the 100th cycle capacity retention rate is calculated using the following formula:
[0107] The capacity retention rate after 100 cycles (%) = 100% × 100th cycle discharge capacity / first cycle discharge capacity.
[0108] Table 2
[0109]
[0110]
[0111] In Table 2, the last row of “Not Added” is the test data of Comparative Application Example 4, in which the negative electrode plate does not use battery additives, and “--” represents no test data for specific surface area / swelling rate.
[0112] Combined with the performance test data in Table 2, it can be seen that the battery additive provided by the present invention includes porous latex particles, which have rich pore structures and large specific surface areas. Through the design and optimization of components, the specific surface areas of Examples 1-6 are 414.7-572 m 2 / g, and has good swelling properties, with a swelling rate of 400-9300%. The battery additive, through the design and optimization of components, makes the negative electrode plate containing it have excellent wettability and liquid absorption capacity. The liquid absorption time of the negative electrode plate containing the battery additive is ≤10s. Compared with the ordinary negative electrode plate without additives, the liquid absorption time is shortened by more than 70%, thereby reducing the duration of the battery injection process and improving production capacity. At the same time, the battery additive has a large amount of voids to store electrolyte, significantly improves the liquid retention capacity of the plate, enhances lithium ion conduction, and makes the capacity retention rate of the lithium-ion battery 99.0-99.5% after 100 cycles at room temperature, significantly improving the battery's cycle performance.
[0113] The present invention uses the components and structural design of porous latex particles to enable the battery additive to significantly improve the wettability, liquid absorption and liquid retention of the pole piece. Ordinary latex particles (Comparative Examples 1-2) that do not contain the porous structure defined by the present invention cannot effectively improve the wettability of the pole piece, and cannot improve the liquid absorption and liquid retention performance of the pole piece, resulting in poor cycle performance of the lithium ion battery. Conventional liquid retention additives (Comparative Example 3) in the prior art can improve the liquid retention of the pole piece and the cycle performance of the battery to a certain extent, but their effect has great limitations, and there is no significant improvement in the liquid absorption time. In addition, by setting the ratio of acidic monomers to other monomers and the ratio of monomers to seed emulsions, the structure, morphology and properties of the porous latex particles can be adjusted and optimized, so that the battery additive can more effectively improve the liquid absorption and liquid retention of the pole piece; if the ratio of acidic monomers, other monomers and seed emulsions exceeds the preferred range of the present invention (Examples 7-10), it will affect the structure and properties of the porous latex particles, and then affect the improvement effect of the battery additive on the wettability of the pole piece.
[0114] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate a battery additive and its preparation method and application, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A battery additive, characterized in that: The battery additive includes porous latex particles; The porous latex particles are obtained by reacting a seed emulsion, an acidic monomer and other monomers and then forming pores with an alkaline substance; The mass ratio of the acidic monomer to the other monomers is (0.1-10.0):1.0; The mass ratio of the sum of the mass of the acidic monomer and other monomers to the seed emulsion is 1.0:(0.1-10.0); The seed emulsion includes any one of pure acrylic emulsion, styrene acrylic emulsion, acetic acid acrylic emulsion, silicone acrylic emulsion, styrene butadiene emulsion, nitrile emulsion, polyvinylidene fluoride emulsion or polytetrafluoroethylene emulsion, or a combination of at least two thereof; The acidic monomer is a polymerizable monomer containing at least one of a carboxyl group, a sulfonic acid group or a phosphoric acid group; The other monomers include any one or a combination of at least two of styrene, (meth)acrylate, acrylonitrile or vinyl acetate; The particle size of the porous latex particles is 0.1-10.0 μm; The specific surface area of the porous latex particles is ≥10m 2 / g; The swelling rate of the porous latex particles is 40%-10000%.
2. The battery additive according to claim 1, characterized in that: The swelling rate of the porous latex particles is 100%-10000%.
3. The battery additive according to claim 1, characterized in that: The acidic monomer includes any one of acrylic acid, methacrylic acid, vinyl phosphate or vinyl sulfonic acid, or a combination of at least two thereof.
4. The battery additive according to claim 1, characterized in that: The alkaline substance is a metal hydroxide.
5. The battery additive according to claim 4, characterized in that: The alkaline substance is any one of sodium hydroxide, lithium hydroxide or potassium hydroxide, or a combination of at least two of them.
6. A method for preparing a battery additive according to any one of claims 1 to 5, characterized in that: The preparation method comprises: reacting seed emulsion, acidic monomer and other monomers in the presence of an initiator to obtain a polymer emulsion; and mixing the polymer emulsion with an alkaline substance to form pores to obtain the battery additive.
7. The preparation method according to claim 6, characterized in that: After the seed emulsion, the acidic monomer and other monomers are mixed, an initiator is added thereto to carry out a reaction.
8. The preparation method according to claim 7, characterized in that: The mixing time is 0.1-2.0h.
9. The preparation method according to claim 6, characterized in that: The initiator includes a water-soluble azo initiator and / or a persulfate.
10. The preparation method according to claim 6, characterized in that: Based on the sum of the weight of the acidic monomer and other monomers being 100%, the weight of the initiator is 0.05-5.00%.
11. The preparation method according to claim 6, characterized in that: The reaction temperature is 60-80°C.
12. The preparation method according to claim 6, characterized in that: The reaction time is 1-12h.
13. The preparation method according to claim 6, characterized in that: The polymer emulsion is mixed with an alkaline substance to make the pH value of the system be 7.0-9.
0.
14. The preparation method according to claim 6, characterized in that: The alkaline substance is a metal hydroxide.
15. The preparation method according to claim 14, characterized in that: The alkaline substance is any one of sodium hydroxide, lithium hydroxide or potassium hydroxide, or a combination of at least two of them.
16. The preparation method according to claim 6, characterized in that: The time of making the hole is 0.5-5.0h.
17. The preparation method according to claim 6, characterized in that: The preparation method comprises the following steps: after mixing the seed emulsion, the acidic monomer and other monomers for 0.1-2.0 hours, adding an initiator thereto, reacting at 60-80° C. for 1-12 hours to obtain a polymer emulsion; adding an alkaline substance to the polymer emulsion to adjust the pH value of the system to 7.0-9.0, forming pores to form porous latex particles, and obtaining the battery additive.
18. An electrode material composition, characterized in that: The electrode material composition comprises the battery additive according to any one of claims 1 to 5.
19. The electrode material composition according to claim 18, characterized in that: The electrode material composition comprises an electrode active material, a conductive agent, a binder and the battery additive.
20. The electrode material composition according to claim 19, characterized in that: Based on 100 parts by weight of the electrode active material, the weight of the battery additive is 0.01-1.00 parts by weight.
21. A battery pole piece, characterized in that: The battery electrode comprises a current collector and a coating disposed on the current collector, wherein the material of the coating comprises the electrode material composition as described in any one of claims 18 to 20.
22. An electrochemical energy storage device, characterized in that: The electrochemical energy storage device comprises at least one of the battery additive according to any one of claims 1 to 5, the electrode material composition according to any one of claims 18 to 20, and the battery electrode according to claim 21.
23. The electrochemical energy storage device according to claim 22, characterized in that: The electrochemical energy storage device includes any one of a lithium ion battery, a sodium ion battery, a supercapacitor, a fuel cell or a solar cell.
Citation Information
Patent Citations
Preparation method of lithium battery slurry and application thereof
CN110061222A
Thick positive electrode piece, preparation method thereof and lithium ion battery
CN113611823A
Wet-rub resistant styrene-acrylic emulsion and preparation thereof
CN101280035A
Collector, electrode structure body, and electrical storage component
CN104904050A